Optimasi Konsentrasi Pelilinan dan Suhu Penyimpanan Buah Manggis dengan Menggunakan Metode Respon Surface - Andriani Lubis; Emmy Darmawati; Sutrisno . (PERTETA, 2009)
Post-harvest handling is less precise cause of most of mangosteen can not be maintained quality afterharvest. This research is expected to give information a waxing combination and the optimum temperatureto maintain the quality of mangosteen. Response Surface Method (RSM) was used to create a mathematicalmodel of the influence of temperature and waxing concentration combined treatment. The experimentwas done using the CCD (Central Composite Design) with storage temperature treatment (X1) 6OC, 8OC,13OC, 18OC, 20OC and waxing concentration (X2) 4%, 5%, 7.5%, 10%, 11%. Quality response that wereobserved were the firmness and total soluble solid (TSS) value.The results showed that of the two qualityparameters, TSS is the best response for analysis using RSM with R2 values of 69.3% and lack of fit for0.093. Mathematical model influence of temperature and waxing TSS response is Y = 16.4600 - 0.9268X1- 0.0561X2 + ε. The model produce the plot surface shaped saddle point with optimum value at 18OCstorage temperature and wax concentration of 7.5%, meaning that in those circumstances the changes inTSS value is minimum during self life.Keywords: mangosteen,response surface method, waxing and storage temperatureDiterima: 26 Maret 2009; Disetujui: 28 Agustus 2009